Radiological presence of vascular loops in the cerebellopontine angle region in patients with unilateral Ménière’s disease - Lei, Ping; Xia, Kaijun; Li, Jing; Liu, Yingzhao; Zhou, Renhong; Liu, Jingjing; Wang, Hongchang; Zhou, Yue; Leng, Yangming; Liu, Bo (European archives of oto-rhino-laryngology, 2023)
Objective The relationship between vascular compression of the vestibulocochlear nerve and audio-vestibular symptoms remains controversial. We aimed to examine the radiological features of vascular loops signs in cerebellopontine angle (CPA) and internal auditory canal (IAC) in patients with unilateral Ménière’s disease (MD). Methods One hundred and thirty-seven patients with unilateral definite MD and 69 control subjects (138 ears) were enrolled. All subjects received magnetic resonance imaging of CPA-IAC. The configuration of vascular loops in CPA-IAC, based on the Kazawa classification system, from MD-affected, non-affected and control ears were compared. The associations between imaging findings and Ménière’s stage, electrocochleogram (EcochG) and caloric test were analyzed. Results (1) Among the MD-affected ears, 6 cases (4.4%) were classified as Kazawa type IA, 27 cases (19.7%) as IB, 60 cases (43.8%) as IIA, and 44 cases (32.1%) as IIB. No significant interaural difference in the distribution of Kazawa's types was found ( x 2 = 4.737, p = 0.578) in unilateral MD patients. (2) The distribution of Kazawa's types were not significantly different between the MD-affected ears and the control subjects ( x 2 = 2.876, p = 0.411). (3) No relationship was found between Kazawa staging of the MD-affected ear and Ménière’s stage ( H = 2.679, p = 0.444), EcochG ( x 2 = 0.827, p = 0.867) and caloric test ( x 2 = 4.116, p = 0.248). Conclusions In patients with unilateral MD, the configuration of vascular loops in CPA-IAC region, measured by Kazawa criteria, did not correlate with the laterality, clinical stage, the results of EcochG and caloric test, suggesting that vascular loops may be natural anatomical variations for patients with MD.